Water resources potential in Co To island and exploitation orientation to use - Dan, Nguyen Van; Quyen, Pham Ba; Thong, Bui Xuan; Thuy, Ho Van; Duy, Hoang Duc (Vietnam Journal of Marine Science and Technology, 2020)
Co To is an island of the Co To district in Quang Ninh province with an area of about 18 km2. Average rainfall on the island is 1,738.8 mm/yr, evaporation is 925 mm/yr. On the island, there are some small streams but they are temporary flow in the rainy season, there is not any natural lakes. There are 2 aquifers. The Quaternary aquifer (q) is distributed in a low terrain with area of about 9 km2, thin thickness and saline water is in about half of the area, so it does not make sense for water supply. The fissured aquifer of the ocdovic-silua (o-s) formation is distributed in the high terrain with an area of about 9 km2, this is low potential water layer. The flow rate in the boreholes in the fractured zone due to tectonic activity can be 1–1.5 l/s, it can satisfy small-scale water supply. Potential groundwater reserve of Co To island is 6,472 m3/day, exploitable reserve is 1941 m3/day, exploited reserve level at C1 range is 1,144 m3/day. This can satisfy the water demand for the living of people on the island today. Small-scale groundwater exploitation in the island has just been beginning, but it has the prospect of replication and at the same time there must be reasonable measures to protect and develop water resources to ensure sustainable development and meet the larger water requirements in the future.